Isolation of Jeotgalibacillus malaysiensis sp. nov. from a sandy beach, and emended description of the genus Jeotgalibacillus - Yaakop, A.S.; Chan, Kok Gan; Ee, R.; Kahar, U.M.; Kon, W.C.; Goh, K.M. (Society for General Microbiology, 2015)
A Gram-stain-positive, endospore-forming, rod-shaped bacterial strain, designated D5T, was isolated from seawater collected from a sandy beach in a southern state of Malaysia and subjected to a polyphasic taxonomic study. Sequence analysis of the 16S rRNA gene demonstrated that this isolate belongs to the genus Jeotgalibacillus, with 99.87% similarity toJeotgalibacillus alimentarius JCM 10872T. DNA–DNA hybridization of strain D5T with J. alimentarius JCM 10872T demonstrated 26.3% relatedness. The peptidoglycan type was A1α linked directly to L-lysine as the diamino acid. The predominant quinones identified in strain D5Twere menaquinones MK-7 and MK-8.The major fatty acids were iso-C15:0 and anteiso-C15:0. The G+C content of its DNA was 43.0mol%. The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol and sulfoquinovosyl diacylglycerol, as well as two unknown phospholipids and three unknown lipids. The phenotypic, chemotaxonomic and genotypic data indicated that strain D5T represents a novel species of the genus Jeotgalibacillus, for which the nameJeotgalibacillus malaysiensis sp. nov. is proposed (type strain D5T=DSM 28777T=KCTC33550T). An emended description of the genus Jeotgalibacillus is also provided.